Effects of plant root exudates at different successional stages on the seed germination and seedling growth of subalpine dominant tree species - Liu, Jia; Xia, Ruixue; Zhao, Wenqiang; Fang, Kai; Kou, Yongping; Liu, Qing (Geoderma, 2024)
•Herb root exudates promote P. asperata, but inhibit B. albosinensis and B. platyphylla.•Root exudates increase soil bacterial richness and diversity.•Soil bacteria have a greater role on seedling growth than soil properties and fungi.•Root exudates affect seedling growth of subalpine trees by regulating soil bacteria. Root exudates play an important role in belowground ecological processes, by which plants can regulate the soil ecosystem. However, studies on the effects of root exudates on aboveground plant emergence and growth and thus vegetation regeneration are still lacking, particularly in subalpine forests. In this study, we collected the root exudates of dominant plants at different successional stages (early-stage herbs, mid-stage shrubs and late-stage broadleaf and coniferous trees) in a subalpine region of southwestern China, and used them to condition the soil collected in the field. Using the conditioned soil, a pot experiment on the seed germination and seedling growth of subalpine dominant trees (Betula albosinensis, Betula platyphylla and Picea asperata) was conducted in an artificial climate chamber. The seed germination rate and seedling biomass of the subalpine trees, as well as the soil properties and microbial community structure in the potting soils, were measured. Our results showed that root exudates of different successional stages had significant and distinct effects on the seed germination and seedling growth of the subalpine trees, and these effects differed among the tree species. Specifically, the seed germination rate and seedling biomass of P. asperata were promoted, while those of B. albosinensis and B. platyphylla were inhibited under the addition treatments of the herb root exudates. Furthermore, our study suggested that the soil bacterial community contributed more than soil properties and the fungal community to the variations in the seedling biomass of subalpine trees, and the effects of root exudates on seedling biomass were significantly mediated by the soil bacterial community. Overall, these results implied that root exudates of different successional stages could affect the seedling growth of subalpine trees by regulating soil microbial communities, highlighting the critical role of root exudates during forest succession and providing important insights into the potential rhizosphere mechanisms of forest succession.